2001
DOI: 10.1183/09031936.01.00254101
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between respiratory syncytial virus bronchiolitis and future obstructive airway diseases

Abstract: Relationship between respiratory syncytial virus bronchiolitis and future obstructive airway diseases. G. Wennergren, S. Kristjánsson. #ERS Journals Ltd 2001. ABSTRACT: Evidence from a large number of prospective case-control studies shows that respiratory syncytial virus (RSV) bronchiolitis in infancy is often associated with recurrent wheezing and asthma during subsequent years. However, wheezing tends to diminish and most studies show no significant increase in wheezing compared to controls by school age or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
78
0
7

Year Published

2003
2003
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(88 citation statements)
references
References 99 publications
1
78
0
7
Order By: Relevance
“…Multiple epidemiological studies have clearly demonstrated that history of severe RSV bronchiolitis is frequently associated with subsequent persistent wheezing, childhood asthma or both [9][10][11][12][13]. While murine models of RSV revealed pathogenetic mechanisms related to upregulation of neuroimmune mediating genes [14], the pathogenesis of recurrent wheeze after RSV bronchiolitis is still poorly understood, it also remains unclear what factors govern the selection of some individuals and not others to develop obstructive respiratory symptoms in later childhood [15][16][17]. If RSV is the most frequent cause of LRTIs in young infants, HRVs are the most commonly identified virus involved in wheezing exacerbations in older infants, preschool-aged and school-aged children and adolescents [17][18][19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…Multiple epidemiological studies have clearly demonstrated that history of severe RSV bronchiolitis is frequently associated with subsequent persistent wheezing, childhood asthma or both [9][10][11][12][13]. While murine models of RSV revealed pathogenetic mechanisms related to upregulation of neuroimmune mediating genes [14], the pathogenesis of recurrent wheeze after RSV bronchiolitis is still poorly understood, it also remains unclear what factors govern the selection of some individuals and not others to develop obstructive respiratory symptoms in later childhood [15][16][17]. If RSV is the most frequent cause of LRTIs in young infants, HRVs are the most commonly identified virus involved in wheezing exacerbations in older infants, preschool-aged and school-aged children and adolescents [17][18][19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…The re are a number of epi de mi o lo gi cal stu di es re gar ding the ro le of res pi ra tory vi ru ses and es pe ci ally RSV in re cur rent whe e zing. 8,10,[16][17][18][19] In one of the stu di es investigating the ro le of RSV in the de ve lop ment of ast hma, 12 studies we re re vi e wed and increased risk of ast hma and re cur rent whe ezing af ter RSV in fec ti on was found in the first 36 months, but the re la ti on showed a tendency to dec re a se with age. 18 Hen der son et al 17 similarly found a re la ti on bet we en RSV bronc hi o li tis be fo re 12 months of age and la ter ast hma, but no re la ti on with atopy.…”
Section: Discussionmentioning
confidence: 99%
“…[5][6][7] It has be en shown that many chil dren who ex pe ri en ce RSV in fec ti on in in fancy de ve lop subse qu ent whe e zing epi so des la ter and the risk for ast hma is in cre a sed in tho se in fants. [8][9][10][11][12][13] Whe e zing usu ally re-oc curs af ter acu te bronc hi o li tis in 50% of the ca ses. In cre a sed fre qu ency of whe e zing episo des and ast hma among the chil dren with bronc hi o li tis his tory co uld not be exp la i ned with only atopy and fa mily his tory.…”
Section: Recurrence Of Wheezing Episodes In Children With Respiratorymentioning
confidence: 99%
“…Respiratuar sinsisyal virüs proteinlerinin sekiz tanesi, enfekte hücrelerde ve viriyonlarda bulunan yap›sal proteinlerdir. Yap›sal olmayan NS1 ve NS2 proteinleri, viriyonlarda de¤il yaln›zca enfekte hücrelerde bulunurlar (6,11,12). Respiratuar sinsisyal virüsünün zarf yüzeyindeki iki önemli antijeni olan füzyon (F) ve ba¤lanma (attachment;G) glikoproteinleri immünojen özellik tafl›r.…”
Section: Respiratuar Sinsisyal Virüsunclassified